1994
DOI: 10.1002/1097-0142(19940115)73:2<377::aid-cncr2820730223>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

National survey of ovarian carcinoma IV: Patterns of care and related survival for older patients

Abstract: Background. An analysis was conducted by the American College of Surgeons Cancer Commission evaluating the patterns of care of ovarian cancer patients diagnosed in 1983 and 1988. The purpose of this study was to investigate whether there was a difference in the care patterns of elderly ovarian cancer patients and its impact on survival. Methods. Data were collected from 25 consecutive patients whose disease was diagnosed initially at 904 participating hospitals with cancer programs in 1983 and 1988. The surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(53 citation statements)
references
References 22 publications
2
49
1
Order By: Relevance
“…Less surgery is being performed in the oldest of old [31][32][33]. Patients receiving neoadjuvant chemotherapy do not always eventually receive surgical debulking [34].…”
Section: Discussionmentioning
confidence: 99%
“…Less surgery is being performed in the oldest of old [31][32][33]. Patients receiving neoadjuvant chemotherapy do not always eventually receive surgical debulking [34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been consistently shown that increasing age is associated with lower rates of referral to oncology specialists, lower rates of cytoreductive surgery and lower rates of optimal cytoreduction [31][32][33][34]. Neoadjuvant chemotherapy (NACT) with interval debulking surgery has been shown to be associated with higher rates of optimal cytoreduction, lower perioperative morbidity and mortality rates than primary debulking surgery [35,36].…”
Section: (I) Surgerymentioning
confidence: 99%
“…Advanced chronologic age is often an obstacle to enrollment in a clinical trial [43] or receipt of optimal treatment [9,36,39,92]. However, the older patient subgroup is not homogenous and life expectancy differs within the same age groups in an elderly population [93].…”
Section: Age and Geriatric Assessmentmentioning
confidence: 99%